2014
DOI: 10.1017/s1743921315004548
|View full text |Cite
|
Sign up to set email alerts
|

Full Stokes observations in the He i 1083 nm spectral region covering an M3.2 flare

Abstract: Abstract. We present an exceptional data set acquired with the Vacuum Tower Telescope (Tenerife, Spain) covering the pre-flare, flare, and post-flare stages of an M3.2 flare. The full Stokes spectropolarimetric observations were recorded with the Tenerife Infrared Polarimeter in the He i 1083.0 nm spectral region. The object under study was active region NOAA 11748 on 2013 May 17. During the flare the chomospheric He i 1083.0 nm intensity goes strongly into emission. However, the nearby photospheric Si i 1082.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Spectropolarimetric data of the flare in the Ca II 8542 and He II 10830 Å lines have been analyzed in several works (Penn & Kuhn 1995;Kleint & Judge 2011;Sasso et al 2011;Judge et al 2014Judge et al , 2015Kuckein et al 2015aKuckein et al , 2015b. Using photographic recordings of Stokes I and V profiles in the Ca II H line, Martinez Pillet et al (1990) derived a value of 820(±40)G for B LOS using the weak-field approximation (WFA).…”
Section: Introductionmentioning
confidence: 99%
“…Spectropolarimetric data of the flare in the Ca II 8542 and He II 10830 Å lines have been analyzed in several works (Penn & Kuhn 1995;Kleint & Judge 2011;Sasso et al 2011;Judge et al 2014Judge et al , 2015Kuckein et al 2015aKuckein et al , 2015b. Using photographic recordings of Stokes I and V profiles in the Ca II H line, Martinez Pillet et al (1990) derived a value of 820(±40)G for B LOS using the weak-field approximation (WFA).…”
Section: Introductionmentioning
confidence: 99%
“…These observations covered all of the phases of the flare. Kuckein et al (2015) found that He I Stokes V profiles were substantially larger than the usually larger photospheric Si I Stokes V profiles during the event. In the photosphere, the total magnetic field strength decreased during the flare and recovered its preflare configuration in about 30 minutes after the flare.…”
Section: Introductionmentioning
confidence: 81%
“…Using the chromospheric Ca II 854.2 nm line, she observed Stokes U profiles with asymmetric peaks, while Stokes V profiles indicated magnetic elements of the same polarity with large velocity shifts with respect to the photosphere, decreasing by a factor of two during the observing time. Kuckein et al (2015) reported on high-resolution observations acquired by the Tenerife Infrared Polarimeter (TIP;Martínez Pillet et al 1999) instrument at the German Vacuum Tower Telescope in the near-infrared He I 1083 nm region, covering both the chromospheric He I triplet and the photospheric Si I line at 1082.7 nm during an M3.2 flare that occurred at 08:43 UT on 2013 May 17 in AR NOAA 11758. These observations covered all of the phases of the flare.…”
Section: Introductionmentioning
confidence: 99%
“…• High-cadence spectropolarimetry: The study of fast solar events such as flares [58][59][60] and CMEs or filaments eruptions, 61,62 requires sometimes measurements of the full Stokes vector with a cadence of few minutes or seconds.…”
Section: Data Requirements and Trade-offsmentioning
confidence: 99%